A complex life cycle in a warming planet: gene expression in thermally stressed sponges. Issue 7 (4th February 2013) - Webster, N.; Pantile, R.; Botté, E.; Abdo, D.; Andreakis, N.; Whalan, S.
Abstract Sponges are abundant, diverse and functionally important components of aquatic biotopes with crucial associations for many reef fish and invertebrates. Sponges have strict temperature optima, and mass mortality events have occurred after unusually high temperatures. To assess how sponges may adapt to thermal stress associated with a changing climate, we applied gene expression profiling to both stages of their bipartite life cycles. Adult Rhopaloeides odorabile are highly sensitive to thermal stress (32 °C), yet their larvae can withstand temperatures up to 36 °C. Here, we reveal the molecular mechanisms that underpin these contrasting thermal tolerances, which may provide sponges with a means to successfully disperse into cooler waters. Heat shock protein 70 was induced by increasing temperature in adult sponges, and genes involved in important biological functions including cytoskeleton rearrangement, signal transduction, protein synthesis/degradation, oxidative stress and detoxification were all negatively correlated with temperature. Conversely, gene expression in larvae was not significantly affected until 36 °C when a stress response involving extremely rapid activation of heat shock proteins occurred. This study provides the first transcriptomic assessment of thermal stress on both life history stages of a marine invertebrate facilitating better predictions of the long‐term consequences of climate change for sponge population dynamics.